A phylum-level phylogenetic classification of zygomycete fungi based on genome-scale data. (1st September 2016) - Spatafora, Joseph W.; Chang, Ying; Benny, Gerald L.; Lazarus, Katy; Smith, Matthew E.; Berbee, Mary L.; Bonito, Gregory; Corradi, Nicolas; Grigoriev, Igor; Gryganskyi, Andrii; James, Timothy Y.; O'Donnell, Kerry; et al.
Abstract : Zygomycete fungi were classified as a single phylum, Zygomycota, based on sexual reproduction by zygospores, frequent asexual reproduction by sporangia, absence of multicellular sporocarps, and production of coenocytic hyphae, all with some exceptions. Molecular phylogenies based on one or a few genes did not support the monophyly of the phylum, however, and the phylum was subsequently abandoned. Here we present phylogenetic analyses of a genome-scale data set for 46 taxa, including 25 zygomycetes and 192 proteins, and we demonstrate that zygomycetes comprise two major clades that form a paraphyletic grade. A formal phylogenetic classification is proposed herein and includes two phyla, six subphyla, four classes and 16 orders. On the basis of these results, the phyla Mucoromycota and Zoopagomycota are circumscribed. Zoopagomycota comprises Entomophtoromycotina, Kickxellomycotina and Zoopagomycotina; it constitutes the earliest diverging lineage of zygomycetes and contains species that are primarily parasites and pathogens of small animals (e.g. amoeba, insects, etc.) and other fungi, i.e. mycoparasites. Mucoromycota comprises Glomeromycotina, Mortierellomycotina, and Mucoromycotina and is sister to Dikarya. It is the more derived clade of zygomycetes and mainly consists of mycorrhizal fungi, root endophytes, and decomposers of plant material. Evolution of trophic modes, morphology, and analysis of genome-scale data are discussed.